Layers of Illusions: John Rea’s Hommage à Vasarely - Galaty, James (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2007)
Can lines be heard? Curves? Trajectories? Shapes? These are the questions Canadian composer John Rea asks us in his Hommage à Vasarely (1976), inspired by the work of the Op-Art painter Victor Vasarely. Rea’s work attempts to transfer into sound the ‘optical kinetic’ illusions of movement, bending, and twisting that Vasarely projected onto two dimensions. The lines, shapes, and patterns embedded in the music are best illustrated through score excerpts, pitch-reduction examples and charts schematically displaying the use of the orchestra. Through an understanding of how Rea transfers these geometric patterns and motions into sound, a deeper appreciation of the work, and of the composer, is gained.